Analisis Tingkat Kesehatan Bank Dengan Pendekatan Risk Profile, Good Corporate Governance, Earnings, And Capital Pada PT. BPR Bank Jombang Perseroda - Sabrina Sindy Aulia (Jurnal Manajemen Riset Inovasi, 2024)
This research is aimed at analyzing the level of bank health at PT BPR Bank Jombang Perseroda which was carried out using RGEC method. The data used comes from the financial reports of PT BPR Bank Jombang Perseroda for the 2018-2022 period or five years and 40 company data was found. The RGEC method was employed during the data analysis. Based on the conducted analysis, it was discovered that PT BPR Bank Jombang Perseroda had a fairly excellent rating from 2018 to 2022 (Composite rating 3).